2006
DOI: 10.1038/nn1705
|View full text |Cite
|
Sign up to set email alerts
|

Midline radial glia translocation and corpus callosum formation require FGF signaling

Abstract: Midline astroglia in the cerebral cortex develop earlier than other astrocytes through mechanisms that are still unknown. We show that radial glia in dorsomedial cortex retract their apical endfeet at midneurogenesis and translocate to the overlaying pia, forming the indusium griseum. These cells require the fibroblast growth factor receptor 1 (Fgfr1) gene for their precocious somal translocation to the dorsal midline, as demonstrated by inactivating the Fgfr1 gene in radial glial cells and by RNAi knockdown o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
153
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(162 citation statements)
references
References 50 publications
6
153
1
Order By: Relevance
“…Further support for this idea comes from the analysis of Hs6st1 Ϫ/Ϫ ; Slit2 Ϫ/Ϫ embryos which provide clear evidence for nonepistatic relations between Slit2 and Hs6st1. The absence of glia in the IG and the ectopically located glia that we find in Hs6st1 Ϫ/Ϫ embryos, neither of which is seen in Robo/Slit mutants (Bagri et al, 2002;Andrews et al, 2006), resemble the phenotype reported in conditional FGFR1 Ϫ/Ϫ mutant embryos, which have reduced levels of FGF signaling (Smith et al, 2006;Tole et al, 2006;Moldrich et al, 2010) (compare phenotype summaries in Fig. 11 K and M, N ).…”
Section: Slit1supporting
confidence: 72%
See 2 more Smart Citations
“…Further support for this idea comes from the analysis of Hs6st1 Ϫ/Ϫ ; Slit2 Ϫ/Ϫ embryos which provide clear evidence for nonepistatic relations between Slit2 and Hs6st1. The absence of glia in the IG and the ectopically located glia that we find in Hs6st1 Ϫ/Ϫ embryos, neither of which is seen in Robo/Slit mutants (Bagri et al, 2002;Andrews et al, 2006), resemble the phenotype reported in conditional FGFR1 Ϫ/Ϫ mutant embryos, which have reduced levels of FGF signaling (Smith et al, 2006;Tole et al, 2006;Moldrich et al, 2010) (compare phenotype summaries in Fig. 11 K and M, N ).…”
Section: Slit1supporting
confidence: 72%
“…11 K and M, N ). The normal differentiation and migration of glia which form the GW and IG starts at E14.5 and requires FGF signaling (Smith et al, 2006;Tole et al, 2006). To determine whether reduced FGF signaling could contribute to the Hs6st1 Ϫ/Ϫ callosal phenotype we examined the expression of Sprouty2, a transcriptional target of FGF signaling, at the telencephalic midline.…”
Section: Slit1mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, exogenous application of Fgf9 induces proliferation of Fgfr2/3-positive Müller glial cells in vitro 42 . In the neocortex, analysis of both Fgfr2 and Gfap conditional knockouts and Fgfr1/Fgfr2 and Gfap double mutants showed a decrease in the density of astrocytes in the dorsal neocortex 43 .…”
Section: Discussionmentioning
confidence: 99%
“…These embryonic multipotent progenitors, also called "radial glia," span the entire cortical wall and generate through asymmetric cell divisions neural precursors that eventually differentiate into neurons and migrate to the cerebral cortex (Noctor et al, 2001;Englund et al, 2005;Gal et al, 2006). After the completion of cortical neurogenesis, radial glia transform into astrocytes by retracting their apical (ventricular) processes and migrating upward toward the cortical plate (Schmechel and Rakic, 1979;Pixley and de Vellis, 1984;Smith et al, 2006).…”
Section: Introductionmentioning
confidence: 99%